Upaya Pengelolaan Pemanfaatan Batu Bintang Sebagai Bahan Baku Pembuatan Kerajinan Dengan Menerapkan Usaha Kemitraan Dan Pelatihan Keterampilan Pada Masyarakat Di Desa Leprak Kecamatan Kelabang Kabupaten Bondowoso - Tedjo Asmo Sugeng; Sudiyono Sudiyono (Relawan Jurnal Indonesia, 2017)
Star stone processing system for home industry craft is implemented through community partnership business by applying skills training. Star stone processing system is an alternative solution to the problem finding faced by the business manager. The output target of this program is the application of management of star stones to the maximum so as to provide a positive impact for the absorption of labor and increase the income of the society